Environmental reporting of industrial and supply chain business processes within the context of sustainable development - Yildiz, Turkay; Yercan, Funda (Business: Theory and Practice, 2011)
Green issues in industrial and supply chain business processes have been receiving exponentially growing attention over the past decade. Consumers are demanding green products and services more and more, and on the other side of the marketplace, businesses and industries are now much more responsive to green issues. Furthermore, businesses and industrial systems are, in present conditions, positively reacting to green issues. From an academic perspective, there are considerable numbers of research on this topic in various disciplines. Thus, for the green strategies with respect to the sustainable development, this paper delves into the literature of the significance of sustainability concept with an emphasis on the ecological dimension and then brings a range of essential perspectives along with the applied framework of environmental reporting of industrial and supply chain business processes.